The Alexander romance in Persia and the East - Stoneman, Richard; Erickson, Kyle.; Netton, Ian Richard (Groningen : Barkhuis Publishing : Groningen University Library, 2012)
Alexander the Great of Macedon was no stranger to controversy in his own time. Conqueror of the Greek states, of Egypt and of the Persian Empire as well as many of the principalities of the Indus Valley, he nevertheless became revered as well as vilified. Was he a simply a destroyer of the ancient civilizations and religions of these regions, or was he a hero of the Persian dynasties and of Islam? The conflicting views that were taken of him in the Middle East in his own time and the centuries that followed are still reflected in the tensions that exist between east and west today. The story of Alexander became the subject of legend in the medieval west, but was perhaps even more pervasive in the east. The'Alexander Romance' was translated into Syriac in the sixth century and may have become current in Persia as early as the third century AD. From these beginnings it reached into the Persian national epic, the'Shahnameh', into Jewish traditions, and into the Qur'an and subsequent Arab romance.
Papers from a conference held at the University of Exeter, July 26-29, 2010.
Includes bibliographical references and index.
Keywords: Alexander, -- the Great, -- 356 B.C.-323 B.C. -- Romances -- History and criticism -- Congresses; Alexander, -- the Great, -- 356 B.C.-323 B.C. -- Legends -- Congresses; Persian literature -- History and criticism -- Congresses; Arabic literature -- History and criticism -- Congresses